Attributes of cognitive impairment in patients on maintenance hemodialysis – A cohort study - Geet Gaurav; Deepa Sanjeev Sajjanar; G. V. Naregal; Sanjeev L. Sajjanar (BLDE University Journal of Health Sciences)
BACKGROUND: Chronic kidney disease patients on hemodialysis have higher cognitive impairment than the normal population due to diminishing renal function. Cognitive impairment can be assessed with the Mini-Mental State Examination or the Montreal Cognitive Assessment (MoCA). AIMS AND OBJECTIVES: The current study aims to assess mild cognitive impairment (MCI) using the MoCA examination and to document the attributes of cognitive impairment in patients on maintenance hemodialysis (MHD). MATERIALS AND METHODS: The MoCA examination was administered to all patients in Kannada using the original form SPSS 22.0, developed by SPSS Inc. in Chicago, IL, USA, and was utilized for conducting statistical analyses. RESULTS: Continuous variables were summarized by mean and standard deviation, whereas categorical data were summarized by number and percentage. Categorical variables were assessed using the Chi-square test. A value of P < 0.05 was considered as statistically significant. The mean age of the participants was 44.4 ± 15.1 years, and the mean duration of hemodialysis was 13.8 ± 14 months. About 88.6% of participants (n = 62) showed considerable cognitive impairment and 1.4% had frank dementia. A positive association was noted between cognitive impairment and the conditions of diabetes mellitus and hypertension with a relative risk of 1.02 and 1.11, respectively. The functions of naming and orientation were perfectly correlated with the MoCA scores with r = 0.866 and r = 0.893, respectively. CONCLUSION: The study suggests that the treating physician can stress more on compliance considering the associated cognitive impairment in MHD patients. Parameters such as age, gender, and race/ethnicity influence MCI. This special population needs more attention.